KEMAMPUAN RASIO CAMEL DALAM MEMPREDIKSI PERTUMBUHAN LABA BANK BUMN - Permatasari, Rinny; Saiful, Saiful; Midiastuty, Pratana P (UNIB Press, 2016)
The focus of this study aimed to analyze the influence of financial ratios to future earnings growth consist of CAR, KAP, PPAP, NIM, ROA, ROA, and LDR. The sample in this research is the state-owned banking company listed on the Indonesian Stock Exchange which issued quarterly and annual financial statements for fiscal year 2009 to 2013, namely PT. Bank Mandiri (Persero), Tbk, PT. Bank Rakyat Indonesia (Persero), Tbk, and PT. Bank Negara Indonesia (Persero), Tbk. These three state-owned banks are located in the category of Commercial Bank Business Activities (BUKU) 4 with core capital above Rp. 30 trillion. Data collection methods used are literature and documentation. Data were analyzed using classic assumption test, multiple linear regression analysis test, and test the hypothesis by using the tool SPSS. This study could not provide the empirical evidence on the influence of CAR, KAP, PPAP, NIM, BOPO, ROA, dan LDR to earning growth.